Effect of corn and cowpea planting date on perennial cotton association - Azevedo, Demóstenes Marcos Pedrosa de; Beltrão, Napoleão Esberard de Macêdo; Nóbrega, Laudemiro Baldoíno da (Pesquisa Agropecuaria Brasileira, 2014)
A field experiment was carried out during 1979 through 81 at Patos, PB, Brazil, physiographic zone of Seridó, to study the effects of corn (Zea mays L.) and cowpea (Vigna unguiculata (L) Walp) planting date on perennial cotton, when cultivated together in an associated system. The treatments were: cotton alone; cotton + corn + cowpea, planted simultaneously, corn + cowpea planted 15 days after cotton; corn + cowpea planted 30 days after cotton; corn + cowpea planted 45 days after cotton; cotton + cowpea planted simultaneously, and corn 20 - 30 days after, cotton + corn planted simultaneously, and cowpea 20- 30 days after. The results showed that simultaneous planting date of corn and cowpea reduced considerably cotton production during the first year, but this was the treatment which permitted the largest grain (corn and cowpea) production. Such grains are the main protein and carbohidrate sources in this region. The competitive effects of these crops on cotton were observed only at the first year and the quality of cotton fiber remained unaffected by the intercropping treatments.